Positive reinforcement mediated by midbrain dopamine neurons requires D1 and D2 receptor activation in the nucleus accumbens. - Elizabeth E Steinberg; Josiah R Boivin; Benjamin T Saunders; Ilana B Witten; Karl Deisseroth; Patricia H Janak (PLoS ONE, 2014)
The neural basis of positive reinforcement is often studied in the laboratory using intracranial self-stimulation (ICSS), a simple behavioral model in which subjects perform an action in order to obtain exogenous stimulation of a specific brain area. Recently we showed that activation of ventral tegmental area (VTA) dopamine neurons supports ICSS behavior, consistent with proposed roles of this neural population in reinforcement learning. However, VTA dopamine neurons make connections with diverse brain regions, and the specific efferent target(s) that mediate the ability of dopamine neuron activation to support ICSS have not been definitively demonstrated. Here, we examine in transgenic rats whether dopamine neuron-specific ICSS relies on the connection between the VTA and the nucleus accumbens (NAc), a brain region also implicated in positive reinforcement. We find that optogenetic activation of dopaminergic terminals innervating the NAc is sufficient to drive ICSS, and that ICSS driven by optical activation of dopamine neuron somata in the VTA is significantly attenuated by intra-NAc injections of D1 or D2 receptor antagonists. These data demonstrate that the NAc is a critical efferent target sustaining dopamine neuron-specific ICSS, identify receptor subtypes through which dopamine acts to promote this behavior, and ultimately help to refine our understanding of the neural circuitry mediating positive reinforcement.